2017
DOI: 10.7596/taksad.v6i6.1355
|View full text |Cite
|
Sign up to set email alerts
|

The Improvement of Labor Activity Motivation of Workers in the Process of Their Socialization in the Organization: The Influence of Organizational Culture

Abstract: The article considers organizational culture as the basis for a system of managing motivation of workers' labor activity. It is the control of labor motivation of workers taking into account the features of organizational culture that enables to successfully solve the task of multidimensional and diversified disclosure of human potential in the organization. The authors developed recommendations for improving the motivation of workers' labor activity in the process of their socialization in the organization th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…The motivation system can be seen as a process that allows changes in the methods to achieve employees' motivation through changes in the working environment and conditions (Glaz et al. , 2017).…”
Section: Theoretical Framework and Hypothesesmentioning
confidence: 99%
See 2 more Smart Citations
“…The motivation system can be seen as a process that allows changes in the methods to achieve employees' motivation through changes in the working environment and conditions (Glaz et al. , 2017).…”
Section: Theoretical Framework and Hypothesesmentioning
confidence: 99%
“…For Nientied and Toska (2019), the development of new behaviours by employees are due to the organizational context and the personal experiences of each employee, which allow them to increase, or not, their work motivation. However, Glaz et al. (2017) mention that collective motivation, i.e.…”
Section: Theoretical Framework and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…Labor motivation is important for human resources management (Glaz & Rusetskaya, 2017;Keizer, 2017;Bridoux, Coeurderoy, & Durand, 2017). Scholars, investigating the influence of internal and external motives, concluded that interactions as the internal motive promote the intensification of innovation activity by high rates of progress.…”
Section: Contemporary Empirical Studies Of Human Resources` Interactionsmentioning
confidence: 99%
“…Literature Review Nahavandi and Malekzadeh (1999), mentioned by Al-Sada, Al-Esmael and Faisal (2017, p.165), refer to motivation as an "inner force that drives individuals to accomplish personal and organizational goals" or a "state of mind, desire, energy, or interest that translates into action". Glaz et al (2017) argue that motivation should be treated like a process that fosters changes in workplace conditions to increase the employees' commitment, productivity, and loyalty toward the organization. In addition, highly motivated employees can be seen as a source of competitive advantage since they are more likely to put in extra effort to fulfill their tasks.…”
Section: Introductionmentioning
confidence: 99%